Sand management of unconsolidated sandstone reservoir - Zhou, Shouwei; Sun, Fujie (Singapore : Wiley Blackwell, 2016)
This book investigates sand production problems in the development of unconsolidated sand reservoirs and suggests novel technical solutions and improvements to sand management issues. This book is divided into six chapters: (1) geologic characteristics of unconsolidated sand heavy oil reservoirs and concept of sand management technology; (2) sand production mechanisms and its effect on reservoir petrophysical quality; (3) sand production quantity prediction and well productivity evaluation methods, especially for fluid-solid coupling prediction model; (4) completion technology for sand management; (5) sand flow in well bore and surface processing; (6) the application of sand management technology in China's Bohai heavy oil field. Readership: Petroleum reservoir engineers and production managers worldwide.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Oil sands; Petroleum -- Prospecting; Petroleum -- Geology; Oil sands; Petroleum -- Geology; Petroleum -- Prospecting; TECHNOLOGY & ENGINEERING / Mining; Electronic books